Negócios na base da pirâmide: uma análise de empresas multinacionais brasileiras - Hahn, Ivanete Schneider (2017)
The business opportunities at the base of the pyramid (BOP) market proposed by Prahalad (2005; 2010) who called the multinational companies to play a role in providing products and services to BOP people instigated the development of this PhD dissertation. BOP's business theory shows that it is possible to serve the poor and make it profitable for companies (HART, 2010). From this perspective, this research was designed to investigate and describe the business of Brazilian multinational companies in BOP markets (in domestic and international context). We studied the companies listed in the FDC Ranking of the Brazilian Multinational Companies 2016, since its capital and control is mainly Brazilian and those companies develop international activities of manufacturing, services, research and development centers, banking agencies, franchises, commercial offices, warehouses and distribution centers abroad. So, we analyzed 49 listed companies. Methodologically, this study followed the principles of a multi-method research. Its operationalization was first based on a bibliographic investigation developed to understand what is considered business at BOP - which was characterized in this research as the company that: develop products to the BOP market; to be in BOP communities, with job creation being an intervention in environmental conditions; invested in training and education for entrepreneurs located in BOP communities; or, financed local infrastructure for BOP communities. In this survey, it was possible to identify two companies' capacities, which can induce organizations to develop business in BOP: social responsibility and innovation. Thus, these theories not only supported field research, but were fundamental theories for the thesis. The second stage of the study was operationalized through research on secondary data, where we used online data about the companies, building a database. It was possible to verify that the Brazilian MNCs do not have business in the BOP market as an approach in the company's global business strategy - but there are companies that are more engaged in business development at BOP, such as Banco Bradesco, Artecola, Vale, Natura, Klabin and Banco do Brasil. Finally, it was not possible to establish a specific group of companies more likely to invest in the BOP market. The industry was not decisive in BOP's market entry, nor companies with innovation and social responsibility as business philosophy, as well as the index of internationalization. It has been found, however, that companies with older operating history are more likely to business at the BOP market, and that companies that are in BOP communities or that provide products to BOP often invest in the development of local BOP entrepreneurs.